(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The concept of "Food as Medicine" highlights the therapeutic potential of edible plants and spices, which have been utilized for centuries in various cultures for their health-promoting properties. This paper explores the pharmacological attributes of commonly consumed plants and spices, examining their bioactive compounds and their effects on human health. By delving into the mechanisms through which these natural substances influence physiological processes, this research emphasizes the role of diet in disease prevention and management. Key phytochemicals such as polyphenols, flavonoids, alkaloids, and terpenoids are analyzed for their antioxidant, anti-inflammatory, antimicrobial, and anticancer activities. The study further investigates how these compounds interact with molecular pathways, including those involved in oxidative stress, inflammation, and cellular signaling, thereby contributing to improved health outcomes. Moreover, the paper discusses the potential of integrating these natural agents into conventional therapeutic regimens, offering a complementary approach to modern medicine. The benefits of dietary interventions using specific plants and spices are also considered in the context of chronic diseases such as cardiovascular disorders, diabetes, and neurodegenerative conditions. While acknowledging the limitations and challenges of translating traditional knowledge into clinical practice, this research underscores the importance of a holistic approach to health, where food is viewed not just as sustenance but as a crucial element in the promotion of well-being. The findings encourage further exploration of the pharmacological properties of edible plants and spices, aiming to bridge the gap between nutrition and medicine.